2009
DOI: 10.1002/elsc.200800081
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and withanolide production of Withania coagulans hairy root cultures

Abstract: Inoculation of leaf sections of Withania coagulans with Agrobacterium tumefaciens strain C58C1 (pRiA4) induced transformed roots with the capacity to produce the most important bioactive compounds of Withania species, withanolide A and withaferin A. The hairy roots obtained showed two morphologies: callus‐like roots (CR) with a high capacity to produce withanolides and typical hairy roots (HR) with faster growth capacity and lower withanolide accumulation. The aux1 gene of pRiA4 was detected by PCR analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Previous phytochemical examination of the whole plant resulted in the isolation of 25 compounds, including 24 withanolides and one dimeric lignan, bispicropodophyllin glucoside. [12] Acacia arabica belongs to family Mimosaceae and is reported for In vitro antibacterial activity [13] Flavonoids, sterols/triterpenoids, alkaloids and phenolics are known to be bioactive antidiabetic principles. [14,15] Flavonoids are known to regenerate the damaged beta cells in the alloxan induced diabetic rats.…”
Section: Experimental Designmentioning
confidence: 99%
“…Previous phytochemical examination of the whole plant resulted in the isolation of 25 compounds, including 24 withanolides and one dimeric lignan, bispicropodophyllin glucoside. [12] Acacia arabica belongs to family Mimosaceae and is reported for In vitro antibacterial activity [13] Flavonoids, sterols/triterpenoids, alkaloids and phenolics are known to be bioactive antidiabetic principles. [14,15] Flavonoids are known to regenerate the damaged beta cells in the alloxan induced diabetic rats.…”
Section: Experimental Designmentioning
confidence: 99%
“…Sterilization of seeds, in vitro culturing of roots and extraction of withaferin-A were carried out according to Mirjalili et al [11]. To extract the withaferin-A, we followed the method reported by Chaurasiya et al [5] with some modifications.…”
Section: Extraction Procedures and Sample Preparationmentioning
confidence: 99%
“…Separations were carried out using a Waters XBridge Shield RP18 (2.1 × 100 mm; 3.5 μm) column. The mobile phase consisted of water (A) and ACN (B) using gradient elution: (time, %B) = (0, 20), (5, 55), (5.5, 80), (5.8, 80), (6,20), (11,20) at a flow rate of 0.4 mL/min. MS/MS analysis was performed on a triple quad-rupole mass spectrometer API 3000 (ABSciex, Ontario, Canada) equipped with a Turbo Ionspray source operating in positive ion mode with the following settings: nebulizer gas (N 2 ) at 10 (arbitrary units), curtain gas (N 2 ) at 12 (arbitrary units), auxiliary gas (N 2 ) at 8000 cc/min and CAD gas (N 2 ) at 6 (arbitrary units).…”
Section: Instruments and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides withanolides, there are a number of phytocompounds listed in Table 1, which exhibit similar properties. Biological activity of withanolides is due to C 28 side chain in which C-22 and C-26 are oxidized and are rearranged in a ergostane framework to form a six-membered lactone ring (Mirjalili et al, 2009). Structure-activity corelation of withanolides has been studied which has revealed that unsaturation at α, β position of ketone ring in ring A and epoxy group at position 5β, 6β in ring B are necessary for withanolides to remain biologically active (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%